Ecophysiological studies of Mediterranean plant species at the Castelporziano estate - Manes, Fausto; Seufert, Günther; Vitale, Marcello (Atmospheric Environment, 1997)
e aim of this work was to characterize the eco-physiological performance of the main plant species of the Castelporziano site by single leaf investigations. We measured the leaf gas exchange of Quercus ilex L., Pinus pinea L., Pistacia lentiscus L. and Asphodelus microcarpus L. for several days. Additionally, the xylem water potential of Quercus ibex, Pinus pinea and Pistacia lentiscus was recorded in order to obtain more physiological background information for the discussion of the trace gas emissions. This study indicates significantly different physiological responses to the different environmental condi- tions. In particular, summer conditions (high values of light, air temperature and low xylem water potentials) caused the depression of photosynthesis in Quercus ibex and Pinus pinea but did not affect photosynthesis of Pistacia lentiscus and Asphodelus microcarpus. This should be taken into account when discussing VOC emission rates and fluxes
Keywords: fluorescence; Phenology; photosynthesis; Transpiration; VOCs; Xylem water potential